Health Programmes in the Opolskie Voivodship as a Base for Project Initiatives — the First Experiences - Bedrunka, Karina (Regional Barometer. Analyses & Prognoses, 2017)
In the light of current and projected demographic problems, it is important to take effective measures in many areas of the regional policy and on many levels of regional policy’s management. Successful fundraising, including the EU funds, aimed at social welfare may significantly affect eliminating social and economic inequalities resulting from unfavourable demographic trends (e.g., aging of the society or expected changes in the labour market) which significantly affect public health. The aim of the following research is to identify ex-ante whether and how barriers in implementation of regional health programmes are identified, especially in reference to diabetes, overweight and obesity as well as support of the mother and child. On practical ground the research aims at formulating recommendations on how to remove barriers and offering solutions that will support effective implementation of programmes through project initiatives co-financed by the European Social Fund (ESF). Ongoing and planned initiatives in the health area are mainly based on the regional health programmes. In this respect Opolskie Voivodship gained experience as one of the first voivodships in the country.